Implementasi Queue Berbasis Linked List Pada Aplikasi Web Manajemen Antrian Print Mahasiswa - Sirlia Sahid; Farzad Sahnadi Pasaribu; Mika Monika Fransiska Simanullang; Muhammad Raihansyah Lubis (GLOBAL SCIENTS PUBLISHER, 2025)
Queue irregularities are a common problem with photocopying services, particularly with student assignment printing. Because there is no clear system for managing the order in which documents are printed, students often have to wait long periods. This can lead to dissatisfaction and confusion. The purpose of this research is to create an interactive web application capable of managing routine print queues using a linked list-based queue structure. A queue system based on the FIFO (First In First Out) principle was created. This allows each student to enter their identity, the files to be printed, and any special notes about their printing needs. The system then displays a real-time queue list, allowing the photocopy operator to download the files in the correct order.